"We just want to look good" - A Qualitative Study into Adolescent Girls and Sun Exposure in the United Kingdom - Curtis, Bethany (2008)
Sun exposure has been identified as the primary cause of the development of skin cancer (Albert & Ostheimer, 2002; Bajdik, 2003, Buller et al, 2006). Adolescents are particularly susceptible as their skin is thinner and more sensitive (Aquilina et al, 2004). Moreover, their reported behaviour (Cinar et al, 2006) denotes them as a high risk population (Clavarino et al, 2005).